PEWARISAN NILAI-NILAI BUDAYA MELALUI PENDIDIKAN ISLAM - Wahyuddin, Wahyuddin (Universitas Islam Negeri Alauddin Makassar, 2019)
ABSTRACTIn connection with this community, education meaningful cultural heritage of the older generation to the younger generation in order to remain sustainable community living in other words, society has cultural values or mores that want passed down to the next generation in order to remain preserved. This century has given great kakuasaan on humanity that has never happened in history. Progress and tremendous technological strength with easy to use and utilized by us today. How does one use these technologies rely on moral maturity is concerned. This was clearly stated by the historian Arnold Toynbee in his British Civilization on Trial reminds us that advances in modern technology requires an emphasis on the moral and spiritual dimensions.